Graphite negative electrode material for lithium battery and preparation method of graphite negative electrode material

By modifying phenolic resin and modified graphene coated graphite materials, the problem of graphite being easy to peel and powder in lithium-ion batteries is solved, the circulation performance and capacity retention rate of lithium-ion batteries are improved, the interface impedance is reduced, and the interface is improved. Fast charging lithium excretion point.

CN119240690AActive Publication Date: 2025-01-03HUNAN SANMO NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411404514.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The graphite, the negative electrode material of the existing lithium-ion battery, is easily peeled off and powdered during charging and discharging, resulting in a degradation of cycling performance, especially under low temperature conditions, and the uneven coating of the phenolic resin leads to the generation of irreversible capacity.

Method used

3-hydroxymethyl-3-ethyloxetane and epoxychlorohydrin react with sodium hydroxide to form a modified phenolic resin, and is coated with natural graphite and modified graphene, and is connected by chemical grafting. Improve the binding force between graphite and phenolic resin, form a more uniform wrapping layer, and improve the capacity retention and impedance of lithium-ion batteries.

Benefits of technology

It improves the capacity retention and rate performance of lithium-ion batteries, reduces the interface impedance, improves the fast charging lithium-ion point, and significantly improves the circulation performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005076308320000101
    Figure BDA0005076308320000101
Patent Text Reader

Abstract

The invention provides a graphite negative electrode material for a lithium battery and a preparation method of the graphite negative electrode material. The preparation method comprises the following steps: (1) preparing modified phenolic resin; (2) adding natural graphite and the modified phenolic resin into a reaction kettle, continuously adding the modified graphene, and stirring, heating and coating in a nitrogen atmosphere, specifically, heating to 150-200 DEG C at a speed of 1-2 DEG C / min, preserving heat for 100-120 minutes, heating to 550-600 DEG C at a speed of 4-6 DEG C / min, preserving heat for 180-200 minutes, and cooling to obtain coated graphite; and (3) carbonizing the coated graphite in an atmosphere furnace, and sieving to obtain the graphite negative electrode material for the lithium battery. When the negative electrode material is used for preparing a lithium battery, the capacity retention ratio is high, the rate capability is good, the impedance is low, and the lithium precipitation point of fast charge is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery materials, and in particular relates to a graphite negative electrode material for a lithium battery and a preparation method thereof. Background Art

[0002] Lithium-ion battery negative electrode material is one of the important components of the battery. It stores lithium ions during charging and releases lithium ions during discharging. Graphite has rapidly attracted widespread attention due to its abundant resources, low price, high reversible capacity, low charge and discharge voltage platform, no voltage hysteresis, and excellent conductivity, making graphite one of the main materials for preparing lithium battery negative electrodes.

[0003] Although graphite is currently the most commonly used negative electrode material for lithium-ion batteries, its interlayer force is weak and the interlayer spacing is smaller than the crystal plane interlayer spacing of graphite intercalation compounds, which will cause the graphite sheets to easily peel off and pulverize during the charge and discharge process, thereby affecting the cycle performance of the battery, especially at low temperatures. In addition, due to the structural defects of graphite itself, there are many active groups on its surface, resulting in a large specific surface area of ​​graphite, which makes the initial charge and discharge efficiency relatively low.

[0004] In order to overcome the above-mentioned shortcomings, the existing technology uses asphalt and phenolic resin to modify graphite to improve the specific capacity and cycle efficiency of graphite materials. However, the carbonization temperature of asphalt coating is high and the energy consumption is relatively large; phenolic resin is easy to form an adhesive system that is easy to settle during stirring or volatilization, resulting in uneven coating on the graphite surface. There will be holes on the surface of the graphite coated with phenolic resin, and contact with the electrolyte will cause the generation of irreversible capacity, thereby reducing the cycle performance of the graphite.

[0005] Therefore, there is an urgent need for a graphite negative electrode material for lithium batteries and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a graphite negative electrode material for lithium battery and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a graphite negative electrode material for a lithium battery, the preparation method comprising the following steps:

[0009] (1) 50-55 parts by weight of 3-hydroxymethyl-3-ethyloxetane (CAS: 3143-02-0), 43-45 parts by weight of epichlorohydrin and 23-25 ​​parts by weight of sodium hydroxide are mixed, and the mixture is reacted at 40-45° C. for 18-20 hours to obtain a reaction raw material; 65-70 parts by weight of the reaction raw material, 20-25 parts by weight of a phenolic resin, 4-6 parts by weight of sodium hydroxide and 160-180 parts by weight of toluene are mixed, the mixture is stirred and heated to 80-85° C., the mixture is reacted for 10-14 hours, the pH is adjusted to neutral, and the toluene is evaporated under reduced pressure to obtain a modified phenolic resin;

[0010] (2) adding natural graphite and modified phenolic resin into a reaction kettle, continuing to add modified graphene, stirring and heating for coating under a nitrogen atmosphere, specifically: first heating to 150-200° C. at 1-2° C. / min, keeping the temperature for 100-120 min, then heating to 550-600° C. at 4-6° C. / min, keeping the temperature for 180-200 min, cooling, and obtaining coated graphite;

[0011] (3) The coated graphite is placed in an atmosphere furnace for carbonization and passed through a 325-mesh sieve to obtain a graphite negative electrode material for a lithium battery.

[0012] Furthermore, in the step (2), the particle size D50 of the natural graphite is 10-30 μm.

[0013] Furthermore, in the step (2), the weight ratio of natural graphite, modified phenolic resin and modified graphene is 100:(3-5):(2-4).

[0014] Further, the phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1: (1.3-1.5): (0.1-0.3); the viscosity of phenolic resin A at 25°C is 20-30 cp, the free phenol content is 3-6 wt%, and the residual carbon content is 23-28 wt%; the viscosity of phenolic resin B at 25°C is 500-800 cp, the free phenol content is 3-7 wt%, and the residual carbon content is 35-40 wt%; the viscosity of phenolic resin C at 25°C is 10000-14000 cp, the free phenol content is 10-12 wt%, and the residual carbon content is 43-47 wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0015] In the prior art, phenolic resin is directly used to coat natural graphite, and the performance of the prepared negative electrode material is not ideal. The present invention modifies the phenolic resin to improve the discharge capacity of the prepared lithium ion battery. And when the phenolic resin with specific parameters is compounded, the capacity retention rate of the lithium ion battery can be improved. Analysis is that the present invention is connected to the chain end oxetane group of the phenolic resin by chemical grafting to obtain an epoxy-modified phenolic resin. The epoxy-modified phenolic resin contains an epoxy group that can form a covalent bond with the active group on the graphite surface, thereby improving the bonding force with the graphite substrate and forming a more uniform coating layer. The modified phenolic resin prepared by compounding in a specific ratio has better fluidity and forms a denser structure on the graphite surface, which can improve the capacity retention rate of the lithium ion battery.

[0016] Furthermore, the preparation method of the modified graphene in step (2) comprises the following steps:

[0017] (1) mixing 1 part by weight of graphene oxide, 7-9 parts by weight of p-phenylenediamine, 0.2-0.3 parts by weight of polyethylene glycol 600 and 15-20 parts by weight of water, and reacting under reflux stirring at 80-85° C. for 4-5 hours to obtain a p-phenylenediamine-modified graphene oxide dispersion;

[0018] (2) Adding hydrazine hydrate to the p-phenylenediamine-modified graphene oxide dispersion, reacting at 80-85° C. for 26-28 hours; centrifuging and vacuum drying to obtain modified graphene.

[0019] Furthermore, the sheet diameter of graphene oxide is 10-20 μm and the thickness is 1-5 nm.

[0020] Furthermore, the mass ratio of hydrazine hydrate to graphene oxide is (2-4):1.

[0021] In order to improve the problems of high impedance and large capacity loss during the charge and discharge process of lithium batteries, and the irrational rate performance of the battery, the present invention attempts to add graphene oxide to the coating material, but the effect is not ideal. The present invention modifies graphene oxide to improve the impedance of lithium batteries. Analysis shows that graphite, modified phenolic resin, and modified graphene can form a stable composite structure, which can improve the diffusion path of lithium ions in graphite, form a conductive network, reduce the resistance to lithium ion migration, and thus reduce the interface impedance.

[0022] Furthermore, the stirring speed in step (2) is 15-25 r / min.

[0023] Furthermore, in step (3), the carbonization temperature is 700-900° C., and the carbonization time is 7-9 hours.

[0024] The present invention also provides a graphite negative electrode material for a lithium battery prepared by the above preparation method.

[0025] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0026] 1. When the negative electrode material of the present invention is prepared into a lithium battery, it has a high capacity retention rate, good rate performance, low impedance, and a high lithium precipitation point for fast charging.

[0027] 2. The present invention modifies the phenolic resin to improve the discharge capacity of the prepared lithium-ion battery. And when the phenolic resin with specific parameters is compounded, the capacity retention rate of the lithium-ion battery can be improved.

[0028] 3. The present invention modifies graphene oxide to improve the impedance of lithium batteries and at the same time increases the lithium deposition point of LG fast charging. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides a graphite negative electrode material for a lithium battery, and the preparation method thereof comprises the following steps:

[0032] (1) 52 parts by weight of 3-hydroxymethyl-3-ethyloxetane (CAS: 3143-02-0), 44 parts by weight of epichlorohydrin and 24 parts by weight of sodium hydroxide were mixed, and reacted at 42° C. for 19 hours to obtain a reaction raw material; 68 parts by weight of the reaction raw material, 23 parts by weight of phenolic resin, 5 parts by weight of sodium hydroxide and 170 parts by weight of toluene were mixed, stirred and heated to 82° C., reacted for 12 hours, adjusted the pH to neutral, and evaporated the toluene under reduced pressure to obtain a modified phenolic resin;

[0033] (2) adding natural graphite with a particle size of D50 of 20 μm and modified phenolic resin into a reaction kettle, and continuing to add modified graphene; the weight ratio of natural graphite, modified phenolic resin, and modified graphene is 100:4:3; stirring, heating, and coating are performed under a nitrogen atmosphere, and the stirring speed is 20 r / min, specifically: first heating to 170°C at 1°C / min, keeping the temperature for 110 min, then heating to 570°C at 5°C / min, keeping the temperature for 190 min, and cooling to obtain coated graphite;

[0034] The phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1:1.4:0.2; the viscosity (25°C) of phenolic resin A is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity (25°C) of phenolic resin B is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity (25°C) of phenolic resin C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0035] The preparation method of the modified graphene comprises the following steps:

[0036] S1: 1 part by weight of graphene oxide, 8 parts by weight of p-phenylenediamine, 0.25 parts by weight of polyethylene glycol 600 and 18 parts by weight of water were mixed, and the mixture was refluxed and stirred at 82° C. for 4.5 hours to obtain a p-phenylenediamine-modified graphene oxide dispersion; the graphene oxide flakes had a diameter of 10-20 μm and a thickness of 1-5 nm.

[0037] S2: Add hydrazine hydrate to the p-phenylenediamine modified graphene oxide dispersion, with the mass ratio of hydrazine hydrate to graphene oxide being 3:1; react at 82°C for 27 hours; centrifuge and vacuum dry to obtain modified graphene.

[0038] (3) The coated graphite is placed in an atmosphere furnace for carbonization at a temperature of 800° C. for 8 h; the graphite is sieved through a 325-mesh sieve to obtain a graphite negative electrode material for a lithium battery.

[0039] Example 2

[0040] This embodiment provides a graphite negative electrode material for a lithium battery, and the preparation method thereof comprises the following steps:

[0041] (1) 50 parts by weight of 3-hydroxymethyl-3-ethyloxetane (CAS: 3143-02-0), 43 parts by weight of epichlorohydrin and 23 parts by weight of sodium hydroxide were mixed and reacted at 40° C. for 18 hours to obtain a reaction raw material; 65 parts by weight of the reaction raw material, 20 parts by weight of phenolic resin, 4 parts by weight of sodium hydroxide and 160 parts by weight of toluene were mixed, stirred and heated to 80° C., reacted for 10 hours, adjusted the pH to neutral, and evaporated the toluene under reduced pressure to obtain a modified phenolic resin;

[0042] (2) adding natural graphite with a particle size of D50 of 10-30 μm and modified phenolic resin into a reaction kettle, and continuing to add modified graphene, the weight ratio of natural graphite, modified phenolic resin and modified graphene is 100:3:2; stirring, heating and coating are carried out under a nitrogen atmosphere, and the stirring speed is 15 r / min, specifically: first heating to 150°C at 1°C / min, keeping warm for 100 min, then heating to 550°C at 4°C / min, keeping warm for 180 min, cooling, and obtaining coated graphite;

[0043] The phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1:1.3:0.1; the viscosity of phenolic resin A at 25°C is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity of phenolic resin B at 25°C is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity of phenolic resin C at 25°C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0044] The preparation method of the modified graphene comprises the following steps:

[0045] S1: 1 part by weight of graphene oxide, 7 parts by weight of p-phenylenediamine, 0.2 parts by weight of polyethylene glycol 600 and 15 parts by weight of water were mixed, and the mixture was refluxed and stirred at 80° C. for 4 hours to obtain a p-phenylenediamine-modified graphene oxide dispersion; the graphene oxide flakes had a diameter of 10-20 μm and a thickness of 1-5 nm.

[0046] S2: Add hydrazine hydrate to the p-phenylenediamine modified graphene oxide dispersion, with the mass ratio of hydrazine hydrate to graphene oxide being 2:1; react at 80° C. for 26 hours; centrifuge and vacuum dry to obtain modified graphene.

[0047] (3) The coated graphite is placed in an atmosphere furnace for carbonization at a temperature of 700° C. for 7 h; the graphite is sieved through a 325-mesh sieve to obtain a graphite negative electrode material for a lithium battery.

[0048] Example 3

[0049] This embodiment provides a graphite negative electrode material for a lithium battery, and the preparation method thereof comprises the following steps:

[0050] (1) 55 parts by weight of 3-hydroxymethyl-3-ethyloxetane (CAS: 3143-02-0), 45 parts by weight of epichlorohydrin and 25 parts by weight of sodium hydroxide were mixed and reacted at 45° C. for 20 hours to obtain a reaction raw material; 70 parts by weight of the reaction raw material, 25 parts by weight of phenolic resin, 6 parts by weight of sodium hydroxide and 180 parts by weight of toluene were mixed, stirred and heated to 85° C., reacted for 14 hours, adjusted the pH to neutral, and evaporated the toluene under reduced pressure to obtain a modified phenolic resin;

[0051] (2) adding natural graphite with a particle size D50 of 10-30 μm and modified phenolic resin into a reaction kettle, and continuing to add modified graphene, the weight ratio of natural graphite, modified phenolic resin and modified graphene is 100:5:4; stirring, heating and coating are carried out under a nitrogen atmosphere, and the stirring speed is 25 r / min, specifically: first heating to 200°C at 2°C / min, keeping warm for 120 min, then heating to 600°C at 6°C / min, keeping warm for 200 min, cooling, and obtaining coated graphite;

[0052] The phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1:1.5:0.3; the viscosity of phenolic resin A at 25°C is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity of phenolic resin B at 25°C is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity of phenolic resin C at 25°C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0053] The preparation method of the modified graphene comprises the following steps:

[0054] S1: 1 part by weight of graphene oxide, 9 parts by weight of p-phenylenediamine, 0.3 parts by weight of polyethylene glycol 600 and 20 parts by weight of water were mixed, and the mixture was refluxed and stirred at 85° C. for 5 h to obtain a p-phenylenediamine-modified graphene oxide dispersion; the graphene oxide flakes had a diameter of 10-20 μm and a thickness of 1-5 nm.

[0055] S2: Add hydrazine hydrate to the p-phenylenediamine modified graphene oxide dispersion, with the mass ratio of hydrazine hydrate to graphene oxide being 4:1; react at 85° C. for 28 hours; centrifuge and vacuum dry to obtain modified graphene.

[0056] (3) The coated graphite is placed in an atmosphere furnace for carbonization at a temperature of 900° C. for a carbonization time of 9 h; the graphite is sieved through a 325-mesh sieve to obtain a graphite negative electrode material for a lithium battery.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is that the modified phenolic resin is replaced by phenolic resin.

[0059] The phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1:1.5:0.3; the viscosity of phenolic resin A at 25°C is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity of phenolic resin B at 25°C is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity of phenolic resin C at 25°C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1:1:1; the viscosity of phenolic resin A at 25°C is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity of phenolic resin B at 25°C is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity of phenolic resin C at 25°C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%. All of them are purchased from Hebei Zetian Chemical Co., Ltd.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the modified graphene is replaced by graphene oxide. The sheet diameter of the graphene oxide is 10-20 μm and the thickness is 1-5 nm.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the preparation method of the modified graphene is different.

[0066] The preparation method of modified graphene comprises the following steps: mixing 1 part of graphene oxide and 10 parts of water by weight, adding sodium carbonate to make the pH value 10, stirring at 60° C. for 3 hours to form a suspension; adding 0.2 parts of hexadecyltrimethylammonium bromide to 10 parts of the suspension, stirring evenly, stirring at 64° C. for 4 hours, filtering, washing, drying, grinding through an 80-mesh sieve to obtain modified graphene.

[0067] Comparative Example 5

[0068] The difference between this comparative example and Example 1 is that in step (2), the weight ratio of natural graphite, modified phenolic resin and modified graphene is 100:2:5.

[0069] Comparative Example 6

[0070] The difference between this comparative example and Example 1 is that the stirring heating coating is carried out, the stirring speed is 20r / min, specifically: the temperature is increased to 570°C at 5°C / min, and the temperature is kept for 300min.

[0071] Performance Testing

[0072] 1. The graphite negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-6 were respectively used to prepare half-cells according to the following methods:

[0073] According to the mass ratio of 95:1:2:2, the graphite negative electrode material, conductive carbon black SP, CMC and SBR were weighed respectively, stirred evenly in water to form a negative electrode slurry, and evenly coated on the copper foil using an applicator. The coated electrode was placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours, and then pressed into a negative electrode; where the compaction density = electrode mass / (thickness of the electrode after rolling-collector thickness). The CR-2430 button cell was assembled in a German Braun glove box filled with argon gas. The electrolyte was 1MLiPF6+EC∶EMC∶DMC=1∶1∶1 (volume ratio), and the metal lithium sheet was the counter electrode.

[0074] The prepared half-cell was tested for discharge capacity and first discharge efficiency on an American Arbin BT2000 battery tester. The discharge capacity and first discharge efficiency were measured in accordance with conventional test methods in the field under the conditions of a charge and discharge voltage range of 0.005 V to 1.0 V and a charge and discharge rate of 0.1C.

[0075] 2. Impedance and fast charging and lithium deposition point

[0076] Impedance (DCIR) refers to the direct current resistance under a specific load and discharge current. The half-cells prepared in Examples 1-3 and Comparative Examples 1-6 are charged to 50% SOC, and the voltage drop of the graphite negative electrode material is calculated over the charging current.

[0077] Quickly Charge Teat (QCT-3C): refers to a fast charge test with an input current of 3C (the current required to fully charge the battery in 1 / 3h).

[0078] Table 1 Performance test results

[0079]

[0080] It can be seen from the above performance test results that the lithium batteries prepared with the negative electrode materials of Examples 1-3 have excellent performance, especially the comprehensive performance of Example 1 is the most outstanding.

[0081] However, the comparative examples are significantly inferior to the embodiments in corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the phenolic resin is not modified, and the discharge capacity decreases. In comparative example 2, the phenolic resin ratio scheme is not used, and it can be seen from the results that the capacity retention effect decreases. In comparative example 3, the graphene oxide is not modified, and the preparation method of the modified graphene in comparative example 4 is different, and the impedance of the lithium battery increases. In comparative example 5, the ratio of modified phenolic resin and modified graphene is different, and the coating conditions in comparative example 6 are different, all of which lead to a decrease in the performance of the lithium battery. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0082] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a graphite negative electrode material for a lithium battery, characterized in that: The preparation method comprises the following steps: (1) 50-55 parts by weight of 3-hydroxymethyl-3-ethyloxetane, 43-45 parts by weight of epichlorohydrin and 23-25 ​​parts by weight of sodium hydroxide are mixed, and the mixture is reacted at 40-45° C. for 18-20 hours to obtain a reaction raw material; 65-70 parts by weight of the reaction raw material, 20-25 parts by weight of a phenolic resin, 4-6 parts by weight of sodium hydroxide and 160-180 parts by weight of toluene are mixed, the mixture is stirred and heated to 80-85° C., the mixture is reacted for 10-14 hours, the pH value is adjusted to neutral, and the toluene is evaporated under reduced pressure to obtain a modified phenolic resin; (2) adding natural graphite and modified phenolic resin into a reaction kettle, continuing to add modified graphene, stirring and heating for coating under a nitrogen atmosphere, specifically: first heating to 150-200° C. at 1-2° C. / min, keeping the temperature for 100-120 min, then heating to 550-600° C. at 4-6° C. / min, keeping the temperature for 180-200 min, cooling, and obtaining coated graphite; (3) The coated graphite is placed in an atmosphere furnace for carbonization and sieved to obtain a graphite negative electrode material for a lithium battery.

2. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: The particle size D50 of the natural graphite in step (2) is 10-30 μm.

3. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: In the step (2), the weight ratio of natural graphite, modified phenolic resin and modified graphene is 100:(3-5):(2-4).

4. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: The phenolic resin is a mixture of phenolic resin A, phenolic resin B and phenolic resin C in a weight ratio of 1: (1.3-1.5): (0.1-0.3); the viscosity of phenolic resin A at 25°C is 20-30cp, the free phenol content is 3-6wt%, and the residual carbon content is 23-28wt%; the viscosity of phenolic resin B at 25°C is 500-800cp, the free phenol content is 3-7wt%, and the residual carbon content is 35-40wt%; the viscosity of phenolic resin C at 25°C is 10000-14000cp, the free phenol content is 10-12wt%, and the residual carbon content is 43-47wt%.

5. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: The method for preparing the modified graphene in step (2) comprises the following steps: (1) mixing 1 part by weight of graphene oxide, 7-9 parts by weight of p-phenylenediamine, 0.2-0.3 parts by weight of polyethylene glycol 600 and 15-20 parts by weight of water, and reacting under reflux stirring at 80-85° C. for 4-5 hours to obtain a p-phenylenediamine-modified graphene oxide dispersion; (2) Adding hydrazine hydrate to the p-phenylenediamine-modified graphene oxide dispersion, reacting at 80-85° C. for 26-28 hours; centrifuging and vacuum drying to obtain modified graphene.

6. The method for preparing a graphite negative electrode material for a lithium battery according to claim 5, characterized in that: The sheet diameter of graphene oxide is 10-20 μm and the thickness is 1-5 nm.

7. The method for preparing a graphite negative electrode material for a lithium battery according to claim 5, characterized in that: The mass ratio of hydrazine hydrate to graphene oxide is (2-4):

1.

8. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: The stirring speed in step (2) is 15-25 r / min.

9. The method for preparing a graphite negative electrode material for a lithium battery according to claim 1, characterized in that: In the step (3), the carbonization temperature is 700-900° C. and the carbonization time is 7-9 hours.

10. A graphite negative electrode material for lithium battery prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for producing bisphenol A novolac epoxy resin through BPA (bisphenol A) heavy ends

    CN103554432A

  • Modification method of carbon material used for lithium ion batteries

    CN104600305A

  • Preparation method of graphene-dopedand carbon-coated modified graphite anode material

    CN104934603A

  • Graphite cathode material coating modification method, graphite cathode material and application

    CN107482203A

  • Modified graphene oxide, modified graphene, and modified graphene epoxy resin dispersion liquid

    CN109666259A

Cited By

  • Pole piece slurry of high-capacity lithium battery for unmanned aerial vehicle and coating process of pole piece slurry

    CN120613348A

  • Pole piece slurry of high-capacity lithium battery for unmanned aerial vehicle and coating process thereof

    CN120613348B

  • Graphite anode material for lithium battery and preparation method therefor

    WO2026077069A1